(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The main purpose of the study. In the context of the development of tourism enterprises in Azerbaijan, it is necessary to identify rational directions for the use of marketing opportunities both at the company and state levels. To achieve this goal, the following tasks have been set: •Assess the role of marketing in marketing an innovative product; •Determining the behavioral characteristics of consumers of tourism products; •Study of experience in the application of marketing technologies in the tourism industry. Research methodology. Organizes research on the competitiveness of national tourism enterprises in domestic and international markets and generalizations from world experience in this field. Importance of research application. Adoption of the concept on development of national cluster of state tourism marketing policy, creation of normative-legal base in accordance with the concept of tourism development in each field included in tourism cluster on the basis of world experience and international tourism standards, development and adoption of "Tourism development in Azerbaijan" program, makes it necessary to carry out activities such as the regulation of tourism activities. The results of the study. The state’s tourism policy must be developed and implemented in terms of time and space. In terms of time, we mean short-term and long-term tourism policies. As a result, the state’s tourism policy serves to increase the efficiency of the national tourism cluster and increase the competitiveness of this sector of the national economy. Originality and scientific novelty of the research. In order to develop the national tourism cluster in Azerbaijan, a set of practical measures for tourism marketing activities for local tourism companies and the Government of Azerbaijan is being developed.